Strategi Copywriting dalam Meningkatkan Kerjasama Pada Telkom Indonesia - Abram Henry Julius; Dinar Ayu Chandra Agustin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Copywriting has a close relationship in a branding, copywriting is a bridge to targeted consumers. Copywriting has become a trend that can be found anywhere from start-up companies to companies that are already developing, which one of which is Telkom Indonesia. Telkom Indonesia uses copywriting as one of the strategies to improve the company's performance in running the launched program. These new programs include the FCC (Fisheries Cyber Center) program. This research aims to see the copywriting strategy in increasing cooperation with Telkom Indonesia. This research used descriptive qualitative method. The method of data collection is through observation, interviews and documentation, while data analysis uses reduction, data presentation and drawing conclusions. The results of the analysis show that Telkom Indonesia's copywriting strategy uses effective communication and applies AIDA theory. So that with the copywriting strategy, Telkom Indonesia can increase cooperation and run the program.